Challenges and opportunities for the management of infectious diseases in Europes' prisons: evidence-based guidance. Issue 7 (July 2019) - Tavoschi, Lara; O'Moore, Éamonn; Hedrich, Dagmar
Summary: People in prison have multiple complex health and social care needs. These are likely to be the result of a combination of overlapping, and sometimes interlinked, risk factors for infection, ill-health, and incarceration, such as problem drug use. Incarceration can represent a unique opportunity to make high-quality health care available to people in prison and to target socially deprived groups who are often medically underserved when living in the community they originate from. In recent years, international and European institutions have increasingly acknowledged the importance of treating prison health as an inseparable component of public health. However, numerous challenges hamper the successful implementation of such a concept, including the need for evidence-based decision making, intersectoral partnerships, and better monitoring systems. New initiatives are ongoing in the EU that might contribute to bring about positive changes, such as the publication of the first evidence-based public health guidance on prevention and control of communicable diseases in prison settings.